The Status of Adolescent Testing and Treatment in PEPFAR-Supported Programs, October 2017 to September 2020. (1st May 2023) - Hrapcak, Susan; Hast, Marisa; Okegbe, Tishina; Gross, Jessica; Williams, Jessica; Patel, Monita; Wolf, Hilary; Siberry, George; Lee, Lana; Wiersma, Steven; Agaba, Patricia; Carpenter, Deborah; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Adolescents have poorer outcomes across the HIV cascade compared with adults. We aimed to assess progress in HIV case finding, antiretroviral treatment (ART), viral load coverage (VLC), and viral load suppression (VLS) among adolescents enrolled in the US President's Emergency Plan for AIDS Relief (PEPFAR)–supported programs over a 3-year period that included the beginning of the COVID-19 pandemic. Methods: We analyzed PEPFAR program data in 28 countries/regions for adolescents aged 10–19 years between year 1 (October 2017to September 2018), year 2 (October 2018 to September 2019), and year 3 (October 2019 to September 2020). We calculated the number and percent change for HIV tests, HIV-positive tests, and total number on ART. Calculated indicators included positivity, percent of positives newly initiated on ART (ART linkage), VLC (percent of ART patients on ART for ≥6 months with a documented viral load result within the past 12 months), and VLS (percent of viral load tests with <1000 copies/mL). Results: Between years 1 and 3, the number of HIV tests conducted decreased by 44.2%, with a 29.1% decrease in the number of positive tests. Positivity increased from 1.3%–1.6%. The number of adolescents receiving ART increased by 10.4%. In addition, ART linkage increased (77.8%–86.7%) as did VLC (69.4%–79.4%) and VLS (72.8%–81.5%). Conclusions: Our findings demonstrate PEPFAR's success in increasing the adolescent treatment cohort. We identified ongoing gaps in adolescent case finding, linkage, VLC, and VLS that could be addressed with a strategic mix of testing strategies, optimal ART regimens, and adolescent-focused service delivery models.